HSF1 deficiency accelerates the transition from pressure overload-induced cardiac hypertrophy to heart failure through endothelial miR-195a-3p-mediated impairment of cardiac angiogenesis. (May 2018) - Wang, Shijun; Wu, Jian; You, Jieyun; Shi, Hongyu; Xue, Xiaoyu; Huang, Jiayuan; Xu, Lei; Jiang, Guoliang; Yuan, Lingyan; Gong, Xue; Luo, Haiyan; Ge, Junbo; et al.
Abstract: Heat shock transcription factor 1 (HSF1) deficiency aggravates cardiac remodeling under pressure overload. However, the mechanism is still unknown. Here we employed microRNA array analysis of the heart tissue of HSF1-knockout (KO) mice to investigate the potential roles of microRNAs in pressure overload-induced cardiac remodeling under HSF-1 deficiency, and the profiles of 478 microRNAs expressed in the heart tissues of adult HSF1-KO mice were determined. We found that the expression of 5 microRNAs was over 2-fold higher expressed in heart tissues of HSF1-KO mice than in those of wild-type (WT) control mice. Of the overexpressed microRNAs, miR-195a-3p had the highest expression level in HSF1-null endothelial cells (ECs). Induction with miR-195a-3p in ECs significantly suppressed CD31 and VEGF, promoted AngII-induced EC apoptosis, and impaired capillary-like tube formation. In vivo, the upregulation of miR-195a-3p accentuated cardiac hypertrophy, increased the expression of β-MHC and ANP, and compromised systolic function in mice under pressure overload induced by transverse aortic constriction (TAC). By contrast, antagonism of miR-195a-3p had the opposite effect on HSF1-KO mice. Further experiments confirmed that AMPKα2 was the direct target of miR-195a-3p. AMPKα2 overexpression rescued the reduction of eNOS and VEGF, and the impairment of angiogenesis that was induced by miR-195a-3p. In addition, upregulation of AMPKα2 in the myocardium of HSF1-null mice by adenovirus-mediated gene delivery enhanced CD31, eNOS and VEGF, reduced β-MHC and ANP, alleviated pressure overload-mediated cardiac hypertrophy and restored cardiac function. Our findings revealed that the upregulation of miR-195a-3p due to HSF1 deficiency impaired cardiac angiogenesis by regulating AMPKα2/VEGF signaling, which disrupted the coordination between the myocardial blood supply and the adaptive hypertrophic response and accelerated the transition from cardiac hypertrophy to heart failure in response to pressure overload. Highlights: HSF1 deficiency causes upregulation of miR-195a-3p. miR-195a-3p suppresses AMPKα2-mediated angiogenesis. miR-195a-3p accelerates cardiac remodeling under pressure overload.